Renal Failure Patients in Disasters - Lempert, Kenneth D. (Disaster Med Public Health Prep, 2019)
Disasters regularly occur, and frequently large numbers of patients treated with maintenance dialysis or with the recent onset of acute kidney injury are put at risk owing to the lack of access to dialysis care precipitating also a kidney failure disaster. The absence of necessary dialysis treatments can result in excessive emergency department visits, hospitalizations, morbidity, or an early death. Those with kidney failure are often evaluated in disaster medical locations or hospitals without nephrologists in attendance. Here we offer guidance for medical personnel evaluating such patients so that dialysis dependent individuals can be properly assessed and managed with the need for urgent dialysis recognized. A disaster dialysis triage system is proposed.